The Effect of Daily Yogurt Supplementation on Inflammation and Bone Biomarkers. (7th June 2021) - McGrail, Lindsay; Noel, Sabrina; Maldonado-Contreras, Ana; Mangano, Kelsey
Abstract: Objectives: To evaluate the effect of daily yogurt intake on markers of inflammation and bone turnover in an 8wk RCT among Caribbean Latino adults with low-grade inflammation, at high-risk for osteoporosis (OP). Methods: Eligible adults ( n = 39) at-risk for OP (FRAX score) reporting <2 s/wk of yogurt intake, provided written informed consent, and participated in 1 study visit/wk for 12wks. Baseline (4wks) and intervention (8wks) assessment included health behavior questionnaires, 24-h dietary recalls (NDSR NCC, University of Minnesota, Minneapolis 2019), fecal collections (OMNIgene GUT), and venipunctures. Participants were randomly assigned to yogurt group (YG) [one 5-ounce container/d, 7/wk] or diet control group (DC). Each serving contained 5 grams protein, 8 grams fat, 16 grams carbohydrates, 170 kcal. Pre- and post-intervention blood evaluated osteocalcin (OC), Procollagen I N-Terminal Propeptide (PINP), and a panel of inflammatory biomarkers. Percent change in biomarkers between groups was assessed using unadjusted and adjusted generalized linear models. Relative abundance of yogurt starter cultures ( Lactobacillus delbrueckii subsp. bulgaricus, Streptococcus thermophilus ) was quantified in the feces by qPCR. Fold change in abundance was tested between groups by independent t-test. Results: Participants were 69% women (all post-menopausal), sedentary, average 70y, BMI 30 kg/m 2, and baseline CRP of 5 mg/L. Baseline characteristics were not significantly different between groups. YG presented with 10.7- and 3.8-fold greater abundance of L. bulgaricus and S. thermophilus, respectively, in feces compared to DC. In unadjusted models, PINP increased 18.2% and OC 14.8% in the YG compared to DC [−1.9% P = 0.007, 0.3% P = 0.047, respectively]. In adjusted models, % increase in PINP remained significant ( P = 0.03) but was attenuated for OC ( P = 0.13). Daily yogurt intake did not change inflammatory biomarkers, compared to DC ( P ≥ 0.1). Conclusions: Daily yogurt intake significantly increased bone formation biomarkers from baseline, suggesting that regular yogurt consumption may protect against OP, independent of inflammatory pathways. Funding Sources: Yogurt in Nutrition Initiative grant by Danone Institute International, American Society for Nutrition, International Osteoporosis Foundation